LINGKUNGAN PERGAULAN REMAJA DI SMP NEGERI 13 HALMAHERA BARAT - Arik Hendra Ilata; Y.D.A. Santie; Veronike E.T Salem; Muhammad Fajar Hidayat; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2022)
Teenagers are found to often engage in deviant behavior, such as brawls or fights between students, abuse of narcotics, illegal drugs, and some teenagers are often found drinking alcohol. The purpose of this study was to determine the social environment of adolescents in SMP Negeri 13 West Halmahera, namely the family environment, school environment and community environment. The method in this study uses a qualitative approach to understand the phenomenon of what is experienced by the research subject descriptively. Data analysis Miles and Huberman that activities in qualitative data analysis are carried out interactively and take place continuously until they are completed. The results of this study are that parents whose children attend SMP Negeri 13 West Halmahera, especially grades VIII and IX do not pay much attention to their children's learning, children's attitudes towards their school are strongly influenced by the level of attention from their parents, and the low economic situation of the family causes parents to focuses more on earning a living and the large number of children makes parents pay less attention to their children's education